2015
DOI: 10.1016/s0140-6736(14)60975-2
|View full text |Cite|
|
Sign up to set email alerts
|

The durability of endovascular coiling versus neurosurgical clipping of ruptured cerebral aneurysms: 18 year follow-up of the UK cohort of the International Subarachnoid Aneurysm Trial (ISAT)

Abstract: SummaryBackgroundPrevious analyses of the International Subarachnoid Aneurysm Trial (ISAT) cohort have reported on the risks of recurrent subarachnoid haemorrhage and death or dependency for a minimum of 5 years and up to a maximum of 14 years after treatment of a ruptured intracranial aneurysm with either neurosurgical clipping or endovascular coiling. At 1 year there was a 7% absolute and a 24% relative risk reduction of death and dependency in the coiling group compared with the clipping group, but the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
300
1
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(321 citation statements)
references
References 13 publications
6
300
1
14
Order By: Relevance
“…Thus, clipping, reputed but not proved, at least for unruptured aneurysms, 31 to be more durable than coiling, is a reasonable option for some of these patients, though the long-term follow-up ISAT data con- firm a low rebleed risk after de novo coiling and long-term outcome superiority over clipping. 9 Patients with large ruptured aneurysms could be offered participation in the ISAT II trial.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, clipping, reputed but not proved, at least for unruptured aneurysms, 31 to be more durable than coiling, is a reasonable option for some of these patients, though the long-term follow-up ISAT data con- firm a low rebleed risk after de novo coiling and long-term outcome superiority over clipping. 9 Patients with large ruptured aneurysms could be offered participation in the ISAT II trial.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ISAT reported that the probability of death or dependency at 2 months, 1 year, and 10 years after treatment were higher in the clipping group. 19,20 Results of the ISAT suggest that short-term outcomes regarding mRS scores and mortality may serve as reasonable predictive markers for long-term outcomes. Fourth, the external validity of the CSC grading system has not been confirmed.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…7,[17][18][19][20][21]26,28,30,31 The International Subarachnoid Aneurysm Trial (ISAT), a large randomized controlled trial (RCT) that compared neurosurgical clipping with endovascular coiling in patients with SAH, demonstrated the superiority of coiling. 20 This finding of the ISAT led to a prominent shift in the pattern of treatment for SAH, with the number of coiling procedures steadily increasing following publication.…”
mentioning
confidence: 99%
“…Finally, the study protocol for the BRAT did not include an anticipated analysis restricted to saccular aneurysms. However, in light of the fact that all other randomized trials comparing clipping and coil- 7 Although the remaining 3 studies 4,5,11 were statistically underpowered, it is noteworthy that the larger 2 of the 3 (i.e., the BRAT 11 and the study by Li et al 5 ) both showed 1-year trends of a magnitude similar to the original ISAT 9 results favoring endovascular treatment. In this analysis of saccular aneurysms in the BRAT, there were 5.5% (p = 0.29) fewer poor outcomes in the coiling group at 1 year, whereas in the study by Li et al there were 9.4% fewer dead or disabled patients in the endovascular treatment group.…”
Section: Discussionmentioning
confidence: 87%